The Assessment and Referral Court List program in the Magistrates Court of Victoria: An Australian study of recidivism. (June 2016) - Chesser, Brianna; Smith, Kenneth H.
Abstract: Mental Health Court programs have been steadily increasing in number since the late 1990s. This paper described the Victorian model of diversion in the Assessment and Referral Court List within the Melbourne Magistrates' Court. The results of a two-year recidivism study suggest that successful completion of the list significantly reduced recidivism rates. Furthermore, this program is also effective at reducing the severity of offending behaviour post-program completion. Several factors that ought to inform the ongoing development of Mental Health Diversionary Courts in Australia are also discussed.